On some classes of sequences defined by sequences of Orlicz functions - Et, M.; Altin, Y.; Choudhary, B.; Tripathy, B. C. (Element, 2006)
In this paper we introduce some new seminormed sequence spaces using a sequence of Orlicz functions and examine some properties of these sequence spaces. Furthermore we introduce Delta(m)(ug) - statistical convergence and give a relation between Delta(m)(ug) - statistical convergence and strongly Delta(m)(ug)- Cesaro summable sequences with respect to an Orlicz function.
Keywords: Orlicz function; sequence spaces; seminorm; statistical convergence